2020
DOI: 10.3390/plants9050585
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis Identifies Candidate Genes Regulating Seed Number per Silique in Arabidopsis thaliana

Abstract: Seed weight and number ultimately determine seed yield. Arabidopsis seed number comprised of silique number and seed number per silique (SNS). Comparing seed development and weight, determinants of seed number remain largely uncharacterized. In this study, taking advantage of 107 available Arabidopsis accessions, genome-wide association analysis (GWAS) was employed to identify the candidate genes regulating SNS. GWAS-based genotype and phenotype association analysis identified 38 most significant SNPs marker s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The phenotype of the crowded ovule in bzr1-1D at stage 9 indicates higher ovule density (the ratio of the ovule number to the placenta length) ( ) ( Jiang et al, 2020 ), and suggests that BR increases seed number not only through promoting placentae elongation but also through promoting ovule primordia initiation. Flowers treated with 2,4-epibrassinolide (eBL) at stage 8-9 exhibited increased DR5 signal, indicating a significantly enhanced auxin response ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The phenotype of the crowded ovule in bzr1-1D at stage 9 indicates higher ovule density (the ratio of the ovule number to the placenta length) ( ) ( Jiang et al, 2020 ), and suggests that BR increases seed number not only through promoting placentae elongation but also through promoting ovule primordia initiation. Flowers treated with 2,4-epibrassinolide (eBL) at stage 8-9 exhibited increased DR5 signal, indicating a significantly enhanced auxin response ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seed size is a key agronomic trait that determines the grain yield and breeding of plants (Shirley et al, 2019). The number and weight of the seed ultimately determine seed yield (Jiang et al, 2020). In this study, we found that as a result of overexpression of each of BrMYC2/3-1/3-2/4-1/4-2, both the seed length and seed weight decreased (Figures 4C,E), while seed number per silique increased except for BrMYC2 OE as compared to Ctrl (Figure 4F).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the seed yield, 30 T3 lines were taken from each genotype. After the siliques matured, the first five incompletely developed siliques were removed from the main inflorescence axis as described before (Jiang et al, 2020). The first intact siliques were then used to assess the number of seeds per silique.…”
Section: Seed Production Evaluationsmentioning
confidence: 99%
“…We have demonstrated that PIN3 positively regulates the seed number per silique and seed density in A. thaliana [49]. However, how PIN3 controls seed number remains unclear.…”
Section: Pin3 Regulates Ovule Number and Pistil Growthmentioning
confidence: 92%
“…To unravel the importance of PIN3 in ovule initiation, we identified two new pin3 mutants SALK_113246 and SALK_126753 and named them as pin3-1 and pin3-2, respectively [49], which have the same names with the two reported pin3 mutants [45]. These mutants are four different alleles.…”
Section: Plos Geneticsmentioning
confidence: 99%